2009
DOI: 10.1073/pnas.0810955106
|View full text |Cite
|
Sign up to set email alerts
|

Genomic basis for stimulated respiration by plants growing under elevated carbon dioxide

Abstract: Photosynthetic and respiratory exchanges of CO2 by plants with the atmosphere are significantly larger than anthropogenic CO2 emissions, and these fluxes will change as growing conditions are altered by climate change. Understanding feedbacks in CO2 exchange is important to predicting future atmospheric [CO2] and climate change. At the tissue and plant scale, respiration is a key determinant of growth and yield. Although the stimulation of C 3 photosynthesis by growth at elevated [CO2] can be predicted with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
163
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(186 citation statements)
references
References 36 publications
19
163
1
3
Order By: Relevance
“…7. Interactions of some of the volatiles like; C 2 H 4 , O 2 , CO 2 , SA/MeSA, JAs and NO on various components of respiratory metabolism was reported by Millar and Day (1996), Fan et al (1997), Yang et al (1998), Ederli et al (2006), Leakey et al (2009) and Wang et al (2010). This shows that different volatiles and gases can affect the status of respiration which in turn is closely linked with the potential shelf-life of plant parts (including fruits) after their harvest (Kader 1987;Kader and Saltveit 2003b;Varoquaux and Ozdemir 2005;Paul and Srivastava 2006;Paul et al 2010b).…”
Section: Water Vapours/water Status In Fruitmentioning
confidence: 98%
“…7. Interactions of some of the volatiles like; C 2 H 4 , O 2 , CO 2 , SA/MeSA, JAs and NO on various components of respiratory metabolism was reported by Millar and Day (1996), Fan et al (1997), Yang et al (1998), Ederli et al (2006), Leakey et al (2009) and Wang et al (2010). This shows that different volatiles and gases can affect the status of respiration which in turn is closely linked with the potential shelf-life of plant parts (including fruits) after their harvest (Kader 1987;Kader and Saltveit 2003b;Varoquaux and Ozdemir 2005;Paul and Srivastava 2006;Paul et al 2010b).…”
Section: Water Vapours/water Status In Fruitmentioning
confidence: 98%
“…Similarly, large number of studies on genome-wide expression profiling of plants grown under high [CO 2 ] have been carried out Leakey et al, 2009;Cseke et al, 2009;Wei et al, 2013). Ribeiro et al (2013) showed that high [CO 2 ] promote plant growth via a complex transcriptional network.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…However, previous studies have focused mainly on the impact of changes in atmospheric CO 2 concentration (hereafter expressed as [CO 2 ]), moisture, and temperature on crop photosynthesis [2][3][4][5][6] and agricultural ecosystem soil respiration [7][8][9][10]. Studies on the response of crop respiration to changes in [CO 2 ], moisture and temperature are still inadequate [11,12]. This restricts accurate assessment of crop respiration and affects accurate simulation of product yield.…”
mentioning
confidence: 99%
“…This restricts accurate assessment of crop respiration and affects accurate simulation of product yield. Although studies of the impacts of [CO 2 ] enrichment on respiration of soybean and rice have been carried out through experiments employing free-air carbon dioxide concentration enrichment (FACE) and open top chambers (OTC), the study results show great divergence [12][13][14][15] and quantitative evaluation of the relationships of dark respiration has not been established yet.…”
mentioning
confidence: 99%